The temple of my familiar ebook - Walker, Alice (The Color Purple, 2011)
The Pulitzer Prize–winning author of The Color Purple weaves a “glorious and iridescent” tapestry of interrelated lives in this New York Times bestseller ( Library Journal ). Includes a new letter written by the author In The Temple of My Familiar , Celie and Shug from The Color Purple subtly shadow the lives of dozens of characters, all dealing in some way with the legacy of the African experience in America. From recent African immigrants, to a woman who grew up in the mixed-race rainforest communities of South America, to Celie’s own granddaughter living in modern-day San Francisco, all must come to understand the brutal stories of their ancestors to come to terms with their own troubled lives.   As Walker follows these astonishing characters, she weaves a new mythology from old fables and history, a profoundly spiritual explanation for centuries of shared African American experience. This ebook features an illustrated biography of Alice Walker including rare photos from the author’s personal collection. The Temple of My Familiar is the 2nd book in the Color Purple Collection, which also includes The Color Purple and Possessing the Secret of Joy.